An introduction to Fintech : the revolution of financial services (Apress, 2023)
Here a complete introduction will be offered to help people understand the world of fintech, what makes up a fintech, success factors, important technologies and what the differences are with insurtech and regtech amongst other evolutions. We will begin with a short definition of what a fintech is and how it is different from any other organization. We will cover the existing market, the major players and the challenges. We will understand the underlying technologies that allow for a fintech startup to function. What You Will Learn Examples that show how big data is changing the playing field What elements make up a successful fintech How do fintech startups use blockchain Who This Video is For Professionals looking for a quick understanding of the fintech landscape.